PERAN PROGRAM PUSAT PEMBELAJARAN KELUARGA (PUSPAGA) DALAM PENCEGAHAN KEKERASAN PADA ANAK: STUDI KASUS KOTA SURABAYA - Intifada Saifullah Fatah Wardana, Laskar (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
Violence against children remains a prevalent issue in society, including in Surabaya. Various forms of violence, ranging from physical, psychological, to sexual abuse, significantly impact children's development and mental health. To address this issue, the Family Learning Center (PUSPAGA) serves as a unit that provides education, counseling, and psychosocial services for families. Through a holistic approach, PUSPAGA aims to enhance parental capacity in child-rearing based on children's rights, effective family communication, and violence prevention. This study aims to explore the role of PUSPAGA in preventing violence against children in Surabaya and assess the effectiveness of its programs. Findings indicate that PUSPAGA's success is supported by strong government commitment, adequate infrastructure, community participation, and competent professionals. However, challenges such as limited socialization, cultural barriers, a shortage of professionals, and accessibility issues in suburban areas persist. Through services such as consultations, counseling, parenting classes, and socialization programs, PUSPAGA positively impacts families. However, program optimization requires stronger synergy between the government, communities, and related stakeholders. Consequently, PUSPAGA significantly contributes to creating a safe, prosperous, and child-friendly family environment, supporting Surabaya's vision as a Child-Friendly City.